The Legal Position Of Marriage Agreements Regarding Land Rights In Mixed Marriages In Indonesia - Thalia Salsabilla, Tadisa; Taruno Muryanto, Yudho; Dyah Kusumawati, Erna (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this article is to analyze the legal position of prenuptial agreements in mixed marriages regarding land rights. The type of research used is normative legal research that investigates the systematics of law. This systematic legal research is conducted on laws and regulations or laws that are in accordance with the topic raised. The results of the study indicate that making a prenuptial agreement for the separation of property in mixed marriages is an effective way to resolve cases related to land rights in mixed marriages. Settlement of land ownership disputes in mixed marriages without a prenuptial agreement in Indonesia is by filing a request for separation of property by one of the husband and wife to the court according to their relative competence. This shows that without a prenuptial agreement, the legal process to protect land rights becomes more complex and requires court intervention. Therefore, a prenuptial agreement is considered important because it provides a more efficient path. According to the author, this settlement is the only best and legal way in the eyes of the law.